Document Verification System Using Image Processing: A Case Study of Kabale Municipality. - Ojara, Walter (Kabale University, 2024)
Document verification is a critical task that ensures the authenticity of business authorities issued by organizations or cooperate bodies and administrative institutions like local government. In this project, we propose a novel approach to document verification using image processing techniques to combat such document forgery which has compromised the revenue collection to the expectation. The proposed system will be designed to automate the verification process and eliminate human error, thereby enhancing the accuracy and efficiency of the process. The system is developed using state-of-the-art image processing algorithms, such as Optical Character Recognition (OCR), to extract text from scanned documents. The extracted text is then processed using various techniques, including image filtering, morphological operations, and feature extraction, to identify unique features to authenticate local government documents issued to the clients. Overall, the proposed document verification system using image processing provides a reliable and efficient solution to the problem of document forgery and has the potential to be adopted by other local administrative units like district councils, and city administrative institutions in Uganda and beyond.